Observation of dry season polyphenism in Melanitis leda at different altitudinal gradients in Nepal - Khanal, Bhaiya (Journal of Natural History Museum, 2018)
Melanitis leda, a shade loving Satyrid is distributed in tropical to temperate parts of the country. Wet Season Form of this butterfly displays paler wings, prominent eyespots and distinct under wing markings. Dry Season Form remains camouflaged with dry leaf litters mostly in undisturbed parts of the forest floor. This form has diminished eyespots with varying underwing markings. The gradient effect varies location wise which can be assumed to develop different phenotypic forms in this species. Nine such forms of Melanitis leda included in this study were recorded from different forest types of Nepal.